(untitled) (Global Journal of Science Frontier Research, 2021)
Sorghum is a strategically important commodity for food security in Cameroon and several African countries. However, the yields remain low because of several constraints among which the variability of the climatic conditions. With the aim of contributing to the improvement of sorghum production, the present study was conducted to evaluate the growth and yield performance of 03 varieties of rain-fed sorghum grown in a dry-weather system in the Sudano sahelian zone.: Maroua-Cameroon. For this purpose a completely randomized block device has been adopted. The parameters of growth, flowering and yield were recorded and analyzed. The results of the analysis show that the three varieties flowered heterogeneously.